2009
DOI: 10.1111/j.1475-6773.2009.00960.x
|View full text |Cite
|
Sign up to set email alerts
|

Organizational and Market Influences on Physician Performance on Patient Experience Measures

Abstract: Objective. To examine the extent to which medical group and market factors are related to individual primary care physician (PCP) performance on patient experience measures. Data Sources. This study employs Clinician and Group CAHPS survey data (n 5 105,663) from 2,099 adult PCPs belonging to 34 diverse medical groups across California. Medical group directors were interviewed to assess the magnitude and nature of financial incentives directed at individual physicians and the adoption of patient experience imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 48 publications
3
35
0
Order By: Relevance
“…Beyond the surgical literature, evidence from a large statewide demonstration suggests that patients' perspectives of care can incentivize providers to improve quality in the primary care setting. 12, 13 It is unclear whether this information can service as a stimulus for quality improvement in the delivery of surgical care.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the surgical literature, evidence from a large statewide demonstration suggests that patients' perspectives of care can incentivize providers to improve quality in the primary care setting. 12, 13 It is unclear whether this information can service as a stimulus for quality improvement in the delivery of surgical care.…”
Section: Introductionmentioning
confidence: 99%
“…Asch et al 18 found that, following the introduction of a PM system, facilities improved not only on PM scores but also on related clinical measures that were not tracked by the PM system. Other studies have found inconsistent relationships between PM and the patient-centeredness of care 19 20. However, none of these studies attempted to identify a comprehensive set of ancillary benefits or to integrate these benefits into a conceptual framework of the effects of PM.…”
mentioning
confidence: 99%
“…Compared to Democrats, Republicans had the lowest odds of supporting taxes for citizens (OR = 0.08, p < 0.001) and children (OR = 0.09, p < 0.001), followed by voters with no party affiliation and independents. In multivariable models, only male gender (OR = 1.49, p < 0.05) and younger age (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) were related to more support for taxes to ensure coverage for military veterans. Using categorical variables for the support questions, i.e., maintaining the 5-point response scale, and ordinal logistic regression to assess the relationship between voter characteristics and support did not alter most of the study conclusions.…”
Section: Resultsmentioning
confidence: 92%
“…Studies find that insured Americans who seek care in communities with high levels of uninsurance are more likely to report unmet medical needs and problems accessing specialty and emergency services compared to other insured Americans [17,18]. These negative externalities are believed to occur because lower community-level demand for health services induces a weaker supply response [19].…”
Section: Externalitiesmentioning
confidence: 94%